Bankruptcy Analysis Of Pt Sri Rejeki Isman Tbk (Using The Springate, Zmijewski, And Grover Method) - Putri, Mia Aulia; Riyanto, Didik; Ningrum, Listya (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2025)
The insolvency of Sritex has emerged as a significant issue, evident from the progressive decline in financial performance over recent years. Governments, investors, and scholars require early detection tools to recognize such risks in the future. This research aims to examine the bankruptcy status of PT Sri Rejeki Isman Tbk (Sritex), which was officially declared bankrupt in 2024, having previously been recognized as one of Indonesia's leading textile companies. This study employs a quantitative methodology and utilizes financial ratio analysis through three prediction models: Springate, Zmijewski, and Grover. The data used are secondary data obtained from Sritex's annual financial statements for the period 2017–2023. All three models indicate that Sritex experienced financial difficulties prior to its formal bankruptcy declaration. The Zmijewski model was the first to detect a decline in financial condition, followed by the Springate and Grover models. This research demonstrates that bankruptcy prediction models are valuable tools for the early identification of insolvency in publicly traded enterprises.